Experiment on separated layer rock failure technology for stress reduction of entry under coal pillar in mining conditions - Liu, Juntao; Shen, Wenlong; Bai, Jianbiao; Shan, Chengfang; Liu, Xudong (Frontiers in Ecology and Evolution, 2023)
Longwall entrance is especially vulnerable to the combined mining of nearby coal seams because of the substantial deformation disaster loaded by the abutment stress caused by the mining disturbance. Changes to the fracture characteristics, movement behavior, and structural morphology of the bearing structure above the coal pillar are recommended using the separated layer rock failure technology (SLRFT) in order to safeguard the entry beneath the coal pillar from high abutment stress. To simulate the impacts of the SLRFT on the decrease of the abutment stress surrounding the entry under the coal pillar under the plane-stress circumstances, two experimental models were created. Abutment stress revolution, roof movement laws, and fracture features were all tracked using three identical monitoring systems in each experimental model. The experimental results indicate that SLRFT generates the shorter caving step length, more layered collapse, higher caving height of the immediate roof, which improves the dilatancy of caving rock mass, the filling rate and compaction degree of the worked-out area. In the ceiling above the worked-out area, the fracture progresses from a non-penetrating horizontal and oblique gaping fracture to stepped closed fractures and piercing fractures. The main roof's subsidence shifts from a linear, slow tendency to a stepped, fast one. The bearing structure changes from two-sides cantilever structure with T type into one-side cantilever structure with basin type. Since the compacted worked-out region has a bigger support area, more of the overburden load is transferred there, weakening the abutment stress around the longwall entry from 12.5 kPa to 3.7 kPa. The stress reduction degree increases with the reduction of the cantilever length of the bearing structure and the increasing of the support coefficient of the compacted worked-out area. These findings illustrate the effectiveness of SLRFT in lowering entrance stress. With the established experimental model, it is possible to evaluate the viability, efficiency, and design of SLRFT under various engineering and geological circumstances.